Integrating Scaffolding and Deliberate Practice Into Focused Cardiac Ultrasound Training: A Simulator Curriculum - Shannon McConnaughey; Rosario Freeman; Sara Kim; Florence Sheehan (Association of American Medical Colleges, 2018)
Introduction Focused cardiac ultrasound (FoCUS) is widely used for the point-of-care evaluation of basic cardiac pathology, and there is a need for efficient and consistent training in this modality. We designed a simulator-based FoCUS curriculum that integrates instructional scaffolding and deliberate practice to create a directed, self-regulated learning experience for novices. The goal of this strategy was to guide the novice's learning efforts more efficiently and moderate cognitive load while retaining the benefits of independent learning. Methods The complex task of learning cardiac ultrasound is broken into discrete steps, with focused didactic information immediately followed by targeted simulator practice for each module. The practice complexity increases through successive modules, and learners ultimately apply their skills by completing unassisted simulator cases. Immediate visual and quantitative feedback is provided by the simulator whenever an ultrasound image was captured during practice. The entire curriculum is self-guided. Results Sixteen nurse practitioners and resident physicians completed this FoCUS curriculum. In comparison to a previously validated, lecture-before-practice-style curriculum, the average time to completion decreased from 8.0 ± 2.5 hours to 4.7 ± 1.9 hours (p < .0001). There was no difference in posttraining cognitive or psychomotor outcomes between the curricula as measured by a simulator posttest. Discussion A curriculum integrating scaffolding and deliberate practice provides a more efficient, but equally effective, means of teaching psychomotor and cognitive skills in FoCUS. These instructional design principles may translate to other operational learning tasks and allow novices to build skills and reach basic competency more rapidly.